2009
DOI: 10.1021/ol900350k
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis of Janus Kinase Inhibitor INCB018424 via an Organocatalytic Aza-Michael Reaction

Abstract: An enantioselective synthesis of INCB018424 via organocatalytic asymmetric aza-Michael addition of pyrazoles (16 or 20) to (E)-3-cyclopentylacrylaldehyde (23) using diarylprolinol silyl ether as the catalyst was developed. Michael adducts (R)-24 and (R)-27 were isolated in good yield and high ee and were readily converted to INCB018424.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
79
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 150 publications
(81 citation statements)
references
References 25 publications
2
79
0
Order By: Relevance
“…In an effort to evaluate the therapeutic potential of JAK inhibition in MPNs, we identified INCB018424, 22 a potent and selective inhibitor of JAK1 and JAK2 with IC 50 values of 3.3nM and 2.8nM, respectively (Table 1). INCB018424 demonstrated modest selectivity against Tyk2 (ϳ 6-fold) and marked selectivity (Ն 130-fold) against JAK3.…”
Section: Identification and Biochemical Characterization Of Incb018424mentioning
confidence: 99%
“…In an effort to evaluate the therapeutic potential of JAK inhibition in MPNs, we identified INCB018424, 22 a potent and selective inhibitor of JAK1 and JAK2 with IC 50 values of 3.3nM and 2.8nM, respectively (Table 1). INCB018424 demonstrated modest selectivity against Tyk2 (ϳ 6-fold) and marked selectivity (Ն 130-fold) against JAK3.…”
Section: Identification and Biochemical Characterization Of Incb018424mentioning
confidence: 99%
“…In addition, JAK2 plays a central role in the signal transduction of erythropoietin and thrombopoietin (Neubauer et al, 1998;Parganas et al, 1998) and has been shown to play a critical role in erythropoiesis and thrombopoiesis in humans. [3][4]pyrimidin-4-yl)-1H-pyrazol-1-yl)-3-cyclopentylpropanenitrile (INCB018424) is an orally active and potent inhibitor of JAKs with greater than 100-fold selectivity against a panel of 26 non-JAK kinases and is in development for the treatment of myeloproliferative neoplasms (Lin et al, 2009;Quintás-Cardama et al, 2010). INCB018424 has demonstrated efficacy in myelofibrosis, the most serious of the chronic myeloproliferative neoplasms for which there is no approved therapy (Verstovsek et al, 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous literature [14], a synthetic strategy was successfully set, starting from commercially available 4-hydroxy-proline leading to the desired organocatalyst in good overall yield (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%